THE EFFECT OF PROCESSING TIME ON THE DIFFUSION BONDING OF A SiCp REINFORCED ALUMINUM MATRIX COMPOSITE WITH A 380 CASTING ALUMINUM ALLOY - Altuner, Hatice Mollaoglu; Topuz, Ahmet (YILDIZ TECHNICAL UNIV, 2011)
The aluminum matrix composites are becoming more popular due to their superior mechanical properties compared with monolithic aluminum alloys. On the other hand, a main problem in expending the application of aluminum matrix composites (AlMMC) is joining difficulties by conventional welding methods. There is a growing interest in diffusion bonding of Al matrix composites due to the problems occur when conventional welding methods are used. Diffusion bonding is a joining technique in which temperature, time and pressure produce, through diffusion, coalescence of the base metals being bonded. In the present work, a 17% SiCp reinforced aluminum matrix composite and a 380 aluminum casting alloy were diffusion bonded at a constant temperature with different processing times. The effect of time on bonding was investigated. Diffusion bonding experiments were carried out at 560 degrees C under 3 MPa pressure for 30, 60 and 90 minutes holding time in vacuum atmosphere The bonded samples were investigated metallographically by means of light microscopy and scanning electron microscope (SEM). Bonding strengths of the samples were determined with shear tests using a specially designed shear test apparatus. The results showed that the bonding strength increases with increasing bonding time. The highest shear strength was obtained after bonding at 560 degrees C under 3 MPa for 90 minutes.
Keywords: Diffusion bonding; SiC; aluminum matrix composite; Engineering